The effect of hybrid SCMC (BYOD) on foreign language anxiety and learning experience in comparison to pure SCMC and FTF communication - Liu, Xuecheng (Frontiers in Psychology, 2023)
This study aims to investigate the impact of using synchronized computer-mediated communication (SCMC) in a face-to-face (FTF) classroom on reducing foreign language anxiety (FLA) and enhancing the learning experience. Fifty Chinese college students participated in a learning activity under three modes: normal FTF classroom (the blank sample), pure SCMC, and hybrid SCMC (BYOD) mode. The study used smartphones, PCs, open internet, and the bring-your-own-device（BYOD）concept for SCMC applications. After completing the learning activity, the students completed the Foreign Language Classroom Anxiety Scale (FLCAS) questionnaires. The students were also asked to complete the perceptional questionnaires to assess their interaction, anxiety, distraction from the internet, and class atmosphere in the three modes. The results showed that the hybrid SCMC (BYOD) mode improved interaction participation compared to the normal FTF classroom mode (the blank sample), while pure SCMC showed no significant improvement. Both SCMC modes reduced FLA compared to the normal FTF classroom mode (the blank sample), but pure SCMC caused a noticeable increase in distraction from the internet and weakened the classroom atmosphere. In contrast, hybrid SCMC (BYOD) mode had a slight increase in distraction and improved the classroom atmosphere. In conclusion, the study suggests that hybrid SCMC (BYOD) mode may offer a more effective approach than pure SCMC to reduce FLA and enhance interaction and learning experience, based on the comparison of FLA, distraction from the internet, and classroom atmosphere. Further research is needed in the field of classroom-based hybrid SCMC usage to enhance the learning experience and interaction, including a more comprehensive assessment of affective factors and the application of Mobile device management technology in the hybrid SCMC (BYOD) mode to mitigate distraction from the internet.